Application of the Hilbert Transform to measurements of liquid–gas flow using gamma ray densitometry. (June 2015) - Hanus, Robert
Graphical abstract: Highlights: Application of the Hilbert Transform to radioisotope two-phase flow investigation. Analysis of signals received from scintillation probes in liquid–gas flow in horizontal pipeline. Cross-correlation method using Hilbert Transform of the measurement signal (CCFHT). CCFHT method provides better metrological properties than the cross-correlation (CCF). Abstract: Measuring parameters of two-phase flows usually requires contactless measuring techniques to be used together alongside advanced methods of signal processing. One of these techniques, which has been employed for many years in measurements of liquid–gas, liquid–solids and gas–solid flows is a method of gamma-ray densitometry. Frequently in such measurements mutually delayed stochastic signals are received from the scintillation detectors. For the analysis of such signals a well-known cross-correlation function (CCF) is used due to the random nature of the signals and the presence of disturbances. This paper applies the Hilbert Transform to the time delay estimation in measurements of two-phase flow performed by using gamma-ray absorption. It presents the selected results of study of the modified CCFHT cross-correlation method, in which a Hilbert Transform of one measured signal is used. The experiments have been carried out for two-phase water–air flow through a horizontal pipeline of 30 mm inner diameter. A sealed 241 Am gamma ray source of 59.5 keV energy has been used in the experiments mentioned above, together with scintillation detectors based on NaI(Tl) crystals. Based on obtained values of time delay the mean velocity of gaseous phase transported by liquid was calculated. It is stated, that the CCFHT method provides better metrological properties than the classical CCF. In the presented experiments combined uncertainties of the gas phase average velocity did not exceed 3.1% for CCF and 0.05% for CCFHT.